2007
DOI: 10.1371/journal.pgen.0030008
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Alström Syndrome Protein, Alms1, in Kidney Ciliogenesis and Cellular Quiescence

Abstract: Premature truncation alleles in the ALMS1 gene are a frequent cause of human Alström syndrome. Alström syndrome is a rare disorder characterized by early obesity and sensory impairment, symptoms shared with other genetic diseases affecting proteins of the primary cilium. ALMS1 localizes to centrosomes and ciliary basal bodies, but truncation mutations in Alms1/ALMS1 do not preclude formation of cilia. Here, we show that in vitro knockdown of Alms1 in mice causes stunted cilia on kidney epithelial cells and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
168
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(183 citation statements)
references
References 49 publications
7
168
0
2
Order By: Relevance
“…We suspect that the greater genetic diversity of our study population has resulted in a breakdown of the linkage disequilibrium in the ALMS1/NAT8 region of the genome, which resulted in a sharper association peak. While the molecular function of ALMS1 is not known, genetic variations within ALMS1 have been implicated in a number of kidney health disorder phenotypes (Chambers et al 2010) including a rare genetic disease called Alström syndrome (Li et al 2007). We further confirmed the association (Nicholson et al 2011) observed for trimethylamine (TMA), thus confirming the strong impact of genetics on the metabolism of a precursor to the major cardiovascular risk factor TMAO (Wang et al 2011).…”
Section: Replication Of Gene-metabolism Associationssupporting
confidence: 68%
“…We suspect that the greater genetic diversity of our study population has resulted in a breakdown of the linkage disequilibrium in the ALMS1/NAT8 region of the genome, which resulted in a sharper association peak. While the molecular function of ALMS1 is not known, genetic variations within ALMS1 have been implicated in a number of kidney health disorder phenotypes (Chambers et al 2010) including a rare genetic disease called Alström syndrome (Li et al 2007). We further confirmed the association (Nicholson et al 2011) observed for trimethylamine (TMA), thus confirming the strong impact of genetics on the metabolism of a precursor to the major cardiovascular risk factor TMAO (Wang et al 2011).…”
Section: Replication Of Gene-metabolism Associationssupporting
confidence: 68%
“…S3 in the supplementary material). The duration of the calcium peaks was in the range of 10-20 seconds, similar to that from single-cell measurements in a recent study using Fura-2 calcium sensor in Dolichos biflorus agglutinin (DBA)-positive mouse embryonic kidney (MEK) cells (Li et al, 2007). Using this experimental setup, we performed an expression microarray analysis to identify genes whose expression levels were altered in response to fluid flow in a PC1-dependent manner.…”
Section: Research Articlesupporting
confidence: 65%
“…Other ciliary proteins have also been implicated in this process, including retinitis-pigmentosa GTPase regulator interacting protein 1-like (RPGRIP1L), which localizes to the basal body (77) and whose expression is decreased in the adipose tissue of mutants for the adjacent FTO gene (78) and the Alström syndrome gene ALMS1, for which obese knockout mice have been generated (79,80). The ALMS1 protein, which localizes to the basal body (81,82), is expressed in the early phases of adipogenesis and may be involved in the conversion of preadipocytes to adipocytes (83). It remains to be determined whether hypothalamic dysfunction alone is sufficient to induce obesity in BBS and other ciliopathies.…”
Section: Molecular Mechanisms Underlying Ciliary Phenotypesmentioning
confidence: 99%